Towards an understanding of the latitudinal patterns in thermal tolerance and vulnerability of woody plants under climate warming - Peng, Shijia; Liu, Yunpeng; Lyu, Tong; Zhang, Xiaoling; Li, Yaoqi; Wang, Zhiheng (EcographyEcography, 2021)
Predicting spatial patterns in thermal tolerance and vulnerability of species under climate warming remains a challenge. Current knowledge is mainly from experiment-based thermal physiology of limited numbers of ectotherms, yet large-scale evaluations on plants remain elusive. Here, using distribution maps with spatial resolutions of 20 × 20 km for 5628 woody species in China, we propose a novel approach, i.e. thermal distribution curves, to describe species' realized thermal niches and then estimate their thermal tolerance and warming risks under projected climate warming in 2050s and 2070s. We find that species' vulnerability and potential local extinction risks within grid cells decrease with latitude and increase with aridity due to narrow thermal tolerance of species located at low latitudes and arid regions. Over 90% of species could still tolerate future warming in most areas, indicating relatively optimistic expectation of potential local extinctions. Our study presents a new framework to quantify climate warming impacts on a large number of species without sufficient physiological information and provides fundamental references for conservation planning under climate change.